Advances in anticancer radiopharmaceuticals. - Jackson, MR; Falzone, N; Vallis, K (2013)
This review highlights recent progress in the development of anticancer radiopharmaceuticals. Molecularly targeted radiotherapy refers to the selective delivery of radionuclides that emit charged particles, such as α particles, β or Auger electrons, to cancer cells via a targeting vector. The discovery of new molecular targets through systems biology and other approaches has widened the scope for radiopharmaceutical development. Innovations in antibody engineering and humanisation, recombinant DNA technology, conjugation chemistry and, increasingly, nanotechnology have provided new approaches to the delivery of radionuclides to cancer cells. The increased availability of radioisotopes that have not traditionally been considered for therapy, such as α particle emitters, has also broadened the indications for targeted radiotherapy.